Foreign experience of legal regulation for separate offenses administrative liability and the possibility of its application in Ukraine - M. Yu. Kriepakova (Law and Safety)
The scientific novelty of the study is that the research is one of the first works that analyzes foreign experience in legal liability for the involvement of a minor in the use of tobacco products, e-cigarettes, liquids used in e-cigarettes, devices for the consumption of tobacco products without their combustion, and uses the developed results to further improve the national legislation governing administrative liability in Ukraine. In accordance with the purpose and objectives of the study, the article uses a set of general theoretical and special scientific methods and techniques of scientific knowledge. Their use is due to a systematic approach, which makes it possible to explore problems in the unity of their social content and legal form. During the work on the article the methods of modeling, forecasting and others were used. The article analyzes the current state of legal regulation of administrative liability for involving a minor in antisocial behavior of such republics as Kazakhstan, Tajikistan, Belarus, Uzbekistan, Latvia. Based on the study, the ways of implementation of foreign experience in Ukraine are outlined, proposals for amendments to the Law of Ukraine "On state regulation of production and circulation of ethyl alcohol, cognac and fruit, alcoholic beverages, tobacco products, liquids used in electronic cigarettes and fuel" and the Code of Ukraine on Administrative Offenses, aimed at regulating the involvement of a minor in the use of tobacco products, electronic cigarettes, liquids used in electronic cigarettes, devices for consumption of tobacco products without their combustion, the implementation of which improves administrative legislation are formulated.